Public safety in the conditions of martial law and mental warfare (Law and Safety, 2022)
The main purpose of the study is to develop proposals and concrete measures to strengthen public security in the conditions of martial law and mental war unleashed against Ukraine. The phenomenon of mental war during martial law and methods of influencing and countering informational attacks on the nation’s mentality have been studied. It has been established that mental warfare is an element of hybrid warfare and its informational component. Information war is a mental war, because it takes place, first of all, for people’s minds, and secondly, for their behavior.Emphasis is placed on the obligation to seize the initiative and force the opponent to defend, otherwise they will spend all their time attacking us. The information array on the content and essence of the concepts “mentality”, “society’s mentality”, “nation’s mentality” and the risks of destructive influence on them in the interest of countering damage to public security have been studied. The mental war for people’s minds means that we must make people immune to the enemy’s “new weapons”, make the enemy’s rules ineffective and carefully leave their field, and in the long run, drag it into ours. For this, we need to create a stable and clear ideology that will provide answers to certain questions and show the path we should follow, the goal we should strive for.The content of the main normative legal acts, which require changes and clarifications in connection with the conduct of mental warfare, has been analyzed. It has been concluded that countering external attacks on the mentality of the nation should have a system-complex nature, which includes, in particular, the organization of training of personnel of this profile in educational institutions of the Ministry of Internal Affairs of Ukraine.Emphasis is placed on the need for a creative approach, which is always unpredictable for the enemy. It is necessary to attract to work in the information space specialists who are able to think outside the box and see the world from a different angle, to get out of the format of leaflets, wall newspapers and linear thinking, when information technologies have immersed the entire active population in the virtual world of percent for 80 % of their free time.
Keywords: martial law; hybrid war; mental war; mentality; public safety; laws of behavior; system of views; moral principles.